HARMONIOUS RELATIONSHIP BETWEEN ISLAM AND SCIENCE IN THE PERSPECTIVE OF THE QUR'AN - Lalu Pattimura Farhan (An-Nahdlah: Jurnal Pendidikan Islam, 2023)
This article discusses the views of the scholars of exegesis on a number of verses related to the relationship between Islam and science (science). This article departs from an article entitled “Islam can give a proper orientation to science and technology development". The article was written by Mehdi Golshani, a lecturer at Sharif University of Technology, Tehran, Iran. After reading Mehdi Golshani's article, the author is in the same position. The author agrees that religion and science run in harmony, there is no conflict between the two. In his presentation on the relationship between religion and science, Mehdi Golshani put forward a number of postulates in the Qur'an. However, the author argues that the postulates put forward by Golshani are not very strong, because they are not supported by the opinions of exegetes. Therefore, this article aims to corroborate Golshani's opinions with some views of scholars' interpretation, about the relationship between Islam and science. In general, a study of exegesis shows that most of the postulates put forward by Golshani are relevant and closely related to science. This article contributed to strengthening the concept of Islamic harmonisation and science